Reciprocal, antipassive and the plurality of relations : parallel developments in Bantu and Atlantic - (:unkn) unknown (My University, 2012)
In almost all the Bantu languages, there is a suffix ¬ an marking reciprocity. Although it is generally uneasy to fine detailed information on the syntactic properties of this suffix in individual languages, it is obvious from the literature that reciprocity is not its only meaning. Actually, there is a great variety of different labels under which this suffix is described but most of them, if not all, might be adequately renamed plurality of relations. In some Bantu languages, there has been a development from reciprocal towards antipassive, which in the extreme cases lead to the complete loss of the reciprocal value. A similar development can be found, at various stages, in languages from the westernmost coast of Africa, namely some languages from the Bak cluster of the Atlantic family. Some differences in the details, and the fact that the suffix itself has different shapes in Bantu and Bak suggest that these developments are parallel ones, regardless of the common (although remote) Niger-Congo affiliation of both language groups. It will be emphasized that such a phenomenon is certainly much overlooked in other languages exhibiting similar patterns of verbal derivation.
Keywords: African Research